Hantavirus Infection in Humans and Rodents, Northwestern Argentina - Noemi Pini; Silvana Levis; Gladys Calderón; Josefina Ramirez; Daniel Bravo; Elena Lozano; Carlos Ripoll; Stephen St. Jeor; Thomas G. Ksiazek; Ruben M. Barquez; Delia Enria (Emerging Infectious Diseases, 2003)
We initiated a study to elucidate the ecology and epidemiology of hantavirus infections in northern Argentina. The northwestern hantavirus pulmonary syndrome (HPS)–endemic area of Argentina comprises Salta and Jujuy Provinces. Between 1997 and 2000, 30 HPS cases were diagnosed in Jujuy Province (population 512,329). Most patients had a mild clinical course, and the death rate (13.3%) was low. We performed a serologic and epidemiologic survey in residents of the area, in conjunction with a serologic study in rodents. The prevalence of hantavirus antibodies in the general human population was 6.5%, one of the highest reported in the literature. No evidence of interhuman transmission was found, and the high prevalence of hantavirus antibody seemed to be associated with the high infestation of rodents detected in domestic and peridomestic habitats.